Production of Paddy Straw Biochar for Amelioration of Coastal Saline Sandy Soil - Das, Madhushree; Kumar, Manish; Kumar, Manoj; Biswas, Kushalindu (International Journal of Bio-resource and Stress Management, 2025)
The pot-based experimental study was undertaken during the pre-kharif season (2022) at CSIR-Institute of Minerals and Materials Technology, Bhubaneswar, Odisha, India. Paddy straw waste pyrolyzed in drum kiln to produce alkaline biochar and utilized for amelioration of saline coastal sandy soil. The soil samples collected from Puri, Odisha was utilized for Mung bean (Vigna radiata var. NVL-516) plant growth experiments (in triplicate) following completely randomized design (CRD). Four levels of salinity (in PSU) i.e. 0 (control), 5 (moderate), 10 (severe) and 20 (extremely severe) were maintained in experimental pots using different volumes of seawater. The three treatment doses of biochar (% weight) i.e. 0.5, 1, and 2 % were applied to each pot. Within 14 days of study period, important soil characteristics (pH, EC, Na, K and Ca), seed germination (%), physiological and growth parameters such as total Chlorophyll, plant height, root length etc. were measured to evaluate the ameliorating influence of biochar on salt stress. The 1% biochar treatment dose resulted into positive influence on germination (enhanced up to 100%), growth and available nutrient concentration up to moderate salinity level (5 PSU). However, biochar treatment alleviating the effect of salt stress, with its increasing doses and salinity beyond 5 PSU showed unsupportive results. Therefore, compared to untreated soil, the lower dose of biochar could enhance the suitability of coastal saline sandy soil for plant growth.